Fibrosis Development in HOCl-Induced Systemic Sclerosis: A Multistage Process Hampered by Mesenchymal Stem Cells - Maria, Alexandre T. J.; Toupet, Karine; Maumus, Marie; Rozier, Pauline; Vozenin, Marie-Catherine; Le Quellec, Alain; Jorgensen, Christian; Noël, Danièle; Guilpain, Philippe (Frontiers in Immunology, 2018)
Objectives: Skin fibrosis is the hallmark of systemic sclerosis (SSc) a rare intractable disease with unmet medical need. We previously reported the anti-fibrotic potential of mesenchymal stem cells (MSCs) in a murine model of SSc. This model, based on daily intra-dermal injections of hypochlorite (HOCl) during six weeks, is an inducible model of the disease. Herein, we aimed at characterizing the development of skin fibrosis in HOCl-induced SSc (HOCl-SSc), and evaluating the impact of MSC infusion during the fibrogenesis process. Methods: After HOCl-SSc induction in BALB/c mice, clinical, histological and biological parameters were measured after three weeks (d21) and six weeks (d42) of HOCl challenge, and three weeks after HOCl discontinuation (d63). Treated-mice received infusions of 2.5x105 MSCs three weeks before sacrifice (d0, d21, d42). Results: HOCl injections induced a two-step process of fibrosis development: first, an ‘early inflammatory phase’, characterized at d21 by highly proliferative infiltrates of myofibroblasts, T-lymphocytes and macrophages. Second, a phase of ‘established matrix fibrosis’, characterized at d42 by less inflammation, but strong collagen deposition as followed by a third phase of ‘spontaneous tissue remodeling’ after HOCl discontinuation. This phase was characterized by partial fibrosis receding, due to enhanced MMP1/TIMP1 balance. MSC treatment reduced skin thickness in the three phases of fibrogenesis, exerting more specialized mechanisms: immunosuppression, abrogation of myofibroblast activation, or further enhancing tissue remodeling, depending on the injection time-point. Conclusion: HOCl-SSc mimics three fibrotic phenotypes of scleroderma, all positively impacted by MSC therapy, demonstrating the great plasticity of MSC, a promising cure for SSc.